Bibliography on ICTR, ICTY and IRMCT 2020 - Le Mécanisme pour les Tribunaux pénaux internationaux (United Nations, 2021)
The bibliography is compiled by the International Residual Mechanism for Criminal Tribunals (IRMCT) Libraries Team from both branches (Arusha and The Hague). It is an invaluable tool for gaining quick access to the literature related to the work of both Ad Hoc Tribunals including the IRMCT ‘Mechanism’. The 2020 edition is an updated version of the previous editions (2011-2018). It includes references to books, journals, periodicals, theses, comments and notes on judicial cases, with a focus on the jurisprudence and work of the IRMCT, the ICTR and the ICTY. It is produced every two years.